Lims system implementation in a non-alcoholic beverage industry: A case study (Research, Society and Development, 2023)
Industries are increasingly investing in the implementation of digital systems for recording data regarding the control and monitoring of their production processes, ensuring reliability and streamlining traceability. The objective of this research was to describe the implementation of Lims in quality control in a non-alcoholic beverage industry, thus performing the evaluation of its applicability in traceability, and the diagnosis of exploring use in the administrative characteristics. For that purpose, the chosen methodology was the qualitative research, through case study and the research of the perception in relation to the software implementation. The results indicate that Lims presents a simple and intuitive interface, adapting to the company's needs and requirements, and presents several functionalities, such as electronic emission and traceability reports. Thus, the research concluded that the implementation of Lims in the quality control of the studied industry was satisfactory, presenting benefits in the information traceability and having as advantages in highlights, the security and control of data, the economy of paper and reduction of physical space for storage, and easy access to information.